2019
DOI: 10.1002/slct.201803679
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of Octanoic Acid over Supported Ni and Mo Catalysts: Effect of Ni/Mo Ratio and Catalyst Recycling

Abstract: Hydrodeoxygenation of octanoic acid over supported NiMo bimetallic catalysts was investigated as a representative of carboxylic acid compounds in bio‐oils. A series of MCM‐41supported Ni and Mo bimetal catalysts were prepared with the wetness impregnation method. The microstructural and physicochemical properties of the fresh and recovered bimetal catalysts were characterized by various methods such as X‐ray diffraction (XRD), Scanning electron microscopy (SEM) and X‐ray photoelectron spectroscopy (XPS), etc..… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
2
8
0
2
Order By: Relevance
“…The above results indicated that a loading of 20 wt.% Ni was quite sufficient for a Ni catalyst supported on montmorillonite, for SDO of WCO under solvent-free conditions. Based on this finding and on the relevant literature [ 20 , 21 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], a catalyst containing 20 wt.% Ni and 2 wt.% Mo co-deposited on the montmorillonite surface was also synthesized and studied. In this catalyst the atomic ratio was equal to 0.94, which is considered very suitable according to the literature [ 20 , 21 , 49 , 50 , 52 , 55 , 56 , 59 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The above results indicated that a loading of 20 wt.% Ni was quite sufficient for a Ni catalyst supported on montmorillonite, for SDO of WCO under solvent-free conditions. Based on this finding and on the relevant literature [ 20 , 21 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], a catalyst containing 20 wt.% Ni and 2 wt.% Mo co-deposited on the montmorillonite surface was also synthesized and studied. In this catalyst the atomic ratio was equal to 0.94, which is considered very suitable according to the literature [ 20 , 21 , 49 , 50 , 52 , 55 , 56 , 59 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 96%
“…Several methodologies have been developed to minimize these problems involving the use of suitable supports, nickel loading, preparation methods and optimized experimental conditions (mainly reaction temperature and hydrogen pressure) [ 11 ], as well as modification of the structure of the supported nickel through development of nickel phosphide [ 44 , 45 , 46 ], nitride [ 47 , 48 ] or carbide catalysts [ 32 , 48 ]. Another very promising prospect for overcoming the above drawbacks and further increasing the efficiency of nickel catalysts is the use of promoters, among which molybdenum oxides are the most effective [ 20 , 21 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. The literature survey indicated that excellent promoting action is observed in molybdenum oxides, mainly for catalysts with a Ni/(Ni+Mo) atomic ratio close to 0.85–0.95 [ 20 , 21 , 49 , 50 , 52 , 55 , 56 , 59 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[121][122][123][124][125]129,131,132,134,138,139,141,143,144,149,162,169]. Αυξανόμενο ενδιαφέρον παρατηρείται στην προσπάθεια ανάπτυξης καταλυτών νικελίου προωθούμενων με οξείδιο του μολυβδαινίου[126,130,140,142,145,147,154,158,160], οξείδιο του βολφραμίου[153] ή οξείδιο του δημητρίου[166]. Ορισμένες εργασίες αφορούν διμεταλλικούς καταλύτες νικελίου-χαλκού [145,161,165], νικελίου-ψευδαργύρου[136,148,150,152,164], νικελίου -παλλαδίου, νικελίου -λευκόχρυσου, και νικελίου -ρουθηνίου[163,165].…”
unclassified
“…Στο σχήμα αναγράφονται οι χρόνοι της κατεργασίας[262] [157]. σεις κάμψης της ομάδας Si-O-Si [158]. Σχήμα 1.5.7Μια παλαιότερη εργασία στόχευε που δημοσιεύθηκε από τον Kumar τους συνεργάτες του στοχεύει πρωτίστως στη μελέτη της εξέλιξης της πορώδους δομής και της ε-[ένταση της όξινης κατεργασίας, κάτι που αντανακλάται στην προοδευτική αύξηση της ειδικής επιφάνειας από 38.03 σε 377.1 m 2 g -1 και του όγκου των πόρων από 0.101 σε 0.805cm 3 g -1 .Αυτά ερμηνεύθηκαν με βάση τo σταδιακό μετασχηματισμό του μοντμοριλλονίτη σε άμορφη σίλικα.…”
unclassified